Pengeluaran R&D dan Kinerja PerusahPengeluaran R&D dan Kinerja Perusahaan Perkebunan yang Terdaftar di Bursa Efek Indonesia (BEI), 2019–2023aan Perkebunan yang Terdaftar di Bursa Efek Indonesia (BEI), 2019–2023 - Yuliansyah, M. Roby; Sembel, Roy; Haymans Manurung, Adler (Jurnal Penelitian Kelapa Sawit, 2025)
This study investigates the impact of R&D expenditure and firm characteristics on the financial performance of Indonesian plantation companies listed on the Indonesia Stock Exchange (IDX) from 2019 to 2023, using quantile regression analysis. Return on Equity (ROE) serves as the performance metric across the 25th, 50th, and 75th quantiles. The results show that R&D expenditure has a significantly negative effect at the median quantile, while Debt to Equity Ratio (DER) negatively affects ROE at both lower and median quantiles. Capital Intensity and Firm Size do not show significant effects, whereas Firm Age has a slight positive effect in the upper quantile. These findings suggest that while R&D investments may burden short-term profitability, they remain essential for long-term performance if managed strategically. The study highlights the importance of partnerships with credible R&D institutions, technological adoption, and government support to overcome sector-specific limitations. Limitations include the sector-specific focus and lack of qualitative dimensions, indicating the need for broader and mixed-method research in the future. Moreover, given the five-year observation period and limited sample size, the findings should be interpreted cautiously and are not intended to be generalized beyond the observed context.